2019
DOI: 10.1177/0950017019836891
|View full text |Cite
|
Sign up to set email alerts
|

Management Millennialism: Designing the New Generation of Employee

Abstract: The idea that society can be divided into discrete generations, each with its own essential characteristics, is treated with caution in sociology, but has had considerable influence among human resource management writers and practitioners. ‘Millennials’ – today’s young adults – are said to bring unique attributes to the workplace that may fit uneasily with current management practice. Given the well-documented weakness of generational categories, both in analysis and practice, this article asks how t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 35 publications
0
23
0
3
Order By: Relevance
“…Authors such as Chaudhuri & Ghoshn (2012) have proposed innovative techniques such as "reverse mentoring" where millennials can teach members of other generations their skills. The generation of millennials is a reality at work and HR managers are in the urgency of implementing the best practices to keep them at work (Williams, 2019) One of the strengths of the present study, is that the sample size is representative of the generation of Millennials and the companies where they work. Another aspect to consider is that there are no studies in Mexico regarding the retention of Millennials at work, and this is a contribution to literature.…”
Section: Discussionmentioning
confidence: 98%
“…Authors such as Chaudhuri & Ghoshn (2012) have proposed innovative techniques such as "reverse mentoring" where millennials can teach members of other generations their skills. The generation of millennials is a reality at work and HR managers are in the urgency of implementing the best practices to keep them at work (Williams, 2019) One of the strengths of the present study, is that the sample size is representative of the generation of Millennials and the companies where they work. Another aspect to consider is that there are no studies in Mexico regarding the retention of Millennials at work, and this is a contribution to literature.…”
Section: Discussionmentioning
confidence: 98%
“…In addition to this, human resources managers should not lose sight of the fact that they must work with the varied generations that are currently in the organizational sphere (Rauvola et al, 2018). There is an urgent need to redesign the working conditions of employees to achieve their expectations (Williams, 2019), although these conditions should be restructured to create a better-quality working life, especially in emerging and underdeveloped countries.…”
Section: Discussionmentioning
confidence: 99%
“…As Kuron, Lyons, Wchweitzer and Ng (2015) reported, there are differences that policy makers should evaluate. For instance, Williams (2019) reported that 98% of Irish employers were facing recruitment challenges and 41% of these employers were dissatisfied with the prospects available. In this sense, the emerging workforce is not meeting the managers´ expectations.…”
Section: Millennials Expectations At Workmentioning
confidence: 99%
“…The appeal of management-by-generation is that it can operate bio-politically which is enabled by the cohort notion of generation it relies upon. In fact, it is because of its combination of tangibility (through markers of age) and elusiveness (due to the conflation of age, cohort, period, and generation) (see Biggs, 2007;Williams, 2020) that allows management-by-generation to operate as a bio-political technology of governance in organizational life. As a result: …'life' has become an independent, objective, and measurable factor, as well as a collective reality that can be epistemologically and practically separated from concrete living beings and the singularity of individual experience.…”
Section: Generations and Bio-politics: Sites Of Appeal And Contestationmentioning
confidence: 99%